Challenges in Supply Chain Management for MSMEs in Maintaining Financial Stability in the Digital Era - Ramadhani, Ananda; Nelly, Nelly; Nengsih, Rita; Ardana, Galang; Yonatada, Ardifal (IC-ITECHS, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as a cornerstone of the economy in various countries, including Indonesia. However, the era of globalization and digitalization presents complex challenges in supply chain management that threaten the financial stability of MSMEs. Some of the key issues faced include dependency on single suppliers, limited access to digital technology, minimal transparency within the supply chain, and rapidly changing global market dynamics. These obstacles often lead to uncertainty in inventory management, increased operational costs, and reduced production efficiency. This article not only identifies these challenges but also provides an in-depth analysis of their impact on the sustainability of MSMEs. Using a solution-based approach, the article offers practical strategies such as supplier diversification to mitigate dependency risks, digital technology integration to enhance supply chain efficiency, and collaboration within supply chain ecosystems to create stronger synergies. Furthermore, the article discusses the role of governments and business communities in supporting digital infrastructure development and providing training for MSMEs to adapt to technological changes.To illustrate the implementation of these strategies, the article includes flowcharts, graphs, and real-world case analyses as practical guides for MSMEs. With this approach, MSMEs are expected to maintain financial stability, improve competitiveness, and achieve sustainable growth amidst the challenges of globalization and digital transformation.